Insomnia and accidents: cross‐sectional study (EQUINOX) on sleep‐related home, work and car accidents in 5293 subjects with insomnia from 10 countries - Léger, Damien; Bayon, Virginie; Ohayon, Maurice M.; Philip, Pierre; Ement, Philippe; Metlaine, Arnaud; Chennaoui, Mounir; Faraut, Brice (Journal of sleep research, 2014)
Summary The link between sleepiness and the risk of motor vehicle accidents is well known, but little is understood regarding the risk of home, work and car accidents of subjects with insomnia. An international cross‐sectional survey was conducted across 10 countries in a population of subjects with sleep disturbances. Primary care physicians administered a questionnaire that included assessment of sociodemographic characteristics, sleep disturbance and accidents (motor vehicle, work and home) related to sleep problems to each subject. Insomnia was defined using the International Classification of Sleep Disorders (ICSD‐10) criteria. A total of 5293 subjects were included in the study, of whom 20.9% reported having had at least one home accident within the past 12 months, 10.1% at least one work accident, 9% reported having fallen asleep while driving at least once and 4.1% reported having had at least one car accident related to their sleepiness. All types of accident were reported more commonly by subjects living in urban compared to other residential areas. Car accidents were reported more commonly by employed subjects, whereas home injuries were reported more frequently by the unemployed. Car accidents were reported more frequently by males than by females, whereas home accidents were reported more commonly by females. Patients with insomnia have high rates of home accidents, car accidents and work accidents related to sleep disturbances independently of any adverse effects of hypnotic treatments. Reduced total sleep time may be one factor explaining the high risk of accidents in individuals who complain of insomnia.